Bidirectional Translation of Promotional Tourism Materials: Challenges and Strategies - Qassem, Mutahar; Sahari, Yousef (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
In today’s globalized world, the effective translation of promotional tourism materials plays a crucial role in bridging cultural and linguistic gaps, thereby enhancing tourist experiences and supporting the growth of the tourism sector. Within this line, this study investigated the translator trainees’ performance on bidirectional translation of tourism-related texts. A sample of 24 Saudi postgraduates specializing in translation participated in the study. They were tasked with translating two promotional tourism texts—one from the Visitsaudi website and the other from the Visittheusa website—representing typical features of both Arabic and English tourist discourse. The trainees’ translations were assessed quantitively and qualitatively in two scenarios: (a) translating from English to Arabic, and (b) the reverse based on three criteria: accuracy, style and clarity. The findings revealed significant challenges in both translation directions, particularly in maintaining style and clarity. The Wilcoxon signed-rank test identified statistically significant differences between the two translation directions, underscoring the inherent challenges in L1 to L2 translation (z = -2.372, p = .018, r = 0.48). The qualitative analysis further indicated that the trainees predominantly employed source-text (ST) oriented strategies, impacting negatively the style, clarity, and accuracy of the target texts (TTs). The trainees’ reliance on source-text (ST) oriented strategies resulted in translations that did not adapt to the linguistic and cultural nuances of the target language, which negatively impacted the quality of the target texts (TTs). The study concludes with recommendations for improving the trainees’ bidirectional translation skills in tourism translation.